2010
DOI: 10.17221/197/2009-cjas
|View full text |Cite
|
Sign up to set email alerts
|

The effect of linseed diet on carcass value traits and fatty acid composition in muscle and fat tissue of fattening pigs

Abstract: ABSTRACT:The aim of the study was to evaluate the effect of linseed in the diet of fattening pigs on carcass value traits and changes in the fatty acid profile in muscle and fat tissue. Thirty crossbred gilts were divided into two groups (control C and experimental L) and fed a commercial feed mixture for fattening pigs. Ground linseed was added to a feed mixture for the experimental group. The average daily gain, lean meat percentage and intramuscular fat content were not affected by the linseed diet but pH1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
11
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
6
11
1
Order By: Relevance
“…Okrouhlá et al (2013) also reported lower content of palmitoleic (C16:1n-7) fatty acid in the study with linseed, but as MUFA can be synthesized in the pig body, their contents in meat are not so important as those of PUFA Kralik et al, 2010). Bečková and Václavková (2010) and Okrouhlá et al (2013) indicated that linseed in the diet of pigs decrease total MUFA; however, no similar results were found in our study. The current results revealed that the MUFA:PUFA ratio decreased by 1.02-0.89 units in the meat of experimental groups 1 and 2, thereby improving the quality of pork.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Okrouhlá et al (2013) also reported lower content of palmitoleic (C16:1n-7) fatty acid in the study with linseed, but as MUFA can be synthesized in the pig body, their contents in meat are not so important as those of PUFA Kralik et al, 2010). Bečková and Václavková (2010) and Okrouhlá et al (2013) indicated that linseed in the diet of pigs decrease total MUFA; however, no similar results were found in our study. The current results revealed that the MUFA:PUFA ratio decreased by 1.02-0.89 units in the meat of experimental groups 1 and 2, thereby improving the quality of pork.…”
Section: Discussioncontrasting
confidence: 59%
“…Corino et al (2008) showed that inclusion of extruded linseed in the diet of pigs increased n-3 PUFA content in both longissimus dorsi muscle and backfat and decreased n-6:n-3 PUFA ratio. Inclusion of 13.4% ground linseed in the diet of pigs increased the content of linoleic and alpha-linolenic acids in the muscle tissue and backfat (Bečková and Václavková, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…On the basis of increased amount of substrate, conversion of ALA to long-chain ω-3 PUFAs increased in the body and resulted in their increased concentration in muscle tissue. Our results agree with those obtained in studies conducted in pigs[2, 11,13,29], chickens[41] and…”
supporting
confidence: 93%
“…The effects of feeding linseed was extensively studied on grower-finisher pigs and had been stated that linseed is an effective feed for increasing the n-3 PUFA content of pig meat and improve the n-6:n-3 PUFA ratio (Rentfrow et al, 2003). Previous findings (Matthews et al, 2000;Riley et al, 2000;Kouba et al, 2003;Corino et al, 2008;Guillevic et al, 2009;Bečková and Václavková, 2010;Nurnberg et al, 2011) reported that inclusion of linseed in pig diets may improve the nutritional value of pork meat without deleteriously affecting organoleptic characteristics, oxidation or colour stability and enhance the levels of n-3 fatty acids, which have a potentially positive health effect in humans.…”
Section: Resultsmentioning
confidence: 99%